Psychological distress and internet addiction among medical students from a Malaysian public university: a comparison between gender - Ching, Siew Mooi; Ali, Hanifatiyah; Cheong, Ai Theng; Salim, Hani Syahida (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Widespread use of the internet is a relatively recent phenomenon that is affecting different cultures worldwide in both positive and negative ways. This study aimed to determine the gender differences in the inter-net addiction among medical students in public university. Methods: 426 medical students from year one to four were invited to participate in the study. For data collection, we used a self-administered questionnaire consisting of socio-demographic and internet usage questions, the Internet Addiction Test (IAT) and the Depression Anxiety and Stress Scales 21 (DASS-21). Results: There were a total of 426 (270 female and 156 male) medical students included in this study. IA was high in both male and female students. There was a higher proportion of male students (44.9%) found to be addicted compared to female students (32.2%). There were positive correlations between the DASS-21 and IAT scores for both male and female students. For female students, longer hours spent online daily (p-value = 0.02), as well as high anxiety (p-value < 0.001) and depression scores (p-value = 0.037) were found to be most strongly associated with IA. Among male students, factors associated with IA were the availability of internet access at home (p-value=0.02) and high anxiety scores (p<0.001). Conclusion: IA was high in both male and female medical students, with higher anxiety raising the risk in both groups. In female students, a higher depression score was also found to be associated with IA.